DIRECT NUMERICAL SIMULATIONS OF TWO-PHASE FLUIDS INTERFACE IN 2D ROTATING DRUMS USING A COUPLED VOF–IBM NUMERICAL APPROACH - (:unkn) unknown (Begell House, 2024)
Rotating drums play important roles in numerous industrial applications, such as mineral processing. This work is focused on the numerical study of the interface evolution in liquid−liquid and liquid−gas phase rotating drums. A new coupling strategy ...
Keywords: Fluidos bifásicos; Simulación numérica